2015
DOI: 10.1515/agp-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Handysurf E-35B electronic profilometer for the study of weathering micro-relief in glacier forelands in SE Iceland

Abstract: ABSTRACT:Dąbski, M. 2015. Application of the Handysurf E-35B electronic profilometer for the study of weathering micro-relief in glacier forelands in SE Iceland. Acta Geologica Polonica, 65 (3), 389-401. Warszawa.This article presents the results of weathering micro-roughness measurements performed with the use of a Handysurf E-35B electronic profilometer, a new tool in geomorphological studies. Measurements were performed on glacially abraded basaltic surfaces within the Little Ice Age (LIA) glacial forelands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…This discussion section links results presented in Figures 1-13 to prior scholarship on cold climate rock-surface processes. The results clearly confirm findings by Rapp [23], Hall [14,[24][25][26], Dixon [27][28][29][30][31][32][33][34][35], Thorn [36][37][38], their collaborators, and others [40][41][42][43][44][45][46][47][105][106][107] on the importance of chemical processes in cold climate geomorphic settings. However, Figures 1-13 also reveal new details of rock-surface chemical l processes at the nanoscale that, we hope, opens the eyes of cold-climate researchers who only perceive "minimal chemical weathering" [39] when they see bare rock (e.g., Figures 1, 11 and 13a).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This discussion section links results presented in Figures 1-13 to prior scholarship on cold climate rock-surface processes. The results clearly confirm findings by Rapp [23], Hall [14,[24][25][26], Dixon [27][28][29][30][31][32][33][34][35], Thorn [36][37][38], their collaborators, and others [40][41][42][43][44][45][46][47][105][106][107] on the importance of chemical processes in cold climate geomorphic settings. However, Figures 1-13 also reveal new details of rock-surface chemical l processes at the nanoscale that, we hope, opens the eyes of cold-climate researchers who only perceive "minimal chemical weathering" [39] when they see bare rock (e.g., Figures 1, 11 and 13a).…”
Section: Discussionsupporting
confidence: 84%
“…Unfortunately, there still exists the assumption by some of "minimal chemical weathering" in cold climates like Antarctica [39]. However, most scholars no longer consider biochemical and chemical rock decay processes as unimportant or even a distant second to physical rock decay, as evidenced by recent research [40][41][42][43][44][45][46][47] and Ph.D. dissertations [48] on cold-climate rock decay not having fight against those prejudiced by the old paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…This supports the previous finding of Dąbski (2009), who worked on post-LIA glacially abraded limestones in the Swiss Alps, as well as Dąbski (2014Dąbski ( , 2015, Evans et al (1999), and Dąbski and Tittenbrun (2013), who worked on freshly deglaciated basalts in Iceland. They showed that SHRT R-values decrease by 5 to 9% in a direction from the youngest to oldest moraines marking the LIA maxima of glaciers.…”
Section: Discussionsupporting
confidence: 90%
“…Paraglacial rock decay can progress rapidly in both periglacial and paraglacial settings (Dixon et al 1984;Ballantyne and Benn 1994;Thorn et al 2001;Dixon et al 2002;French and Guglielmin 2002;Dixon and Thorn 2005;Thorn et al 2006;Dixon 2013) by both abiotic decay processes (Anderson et al 2000) and microorganism-generated decay (Etienne 2002;Etienne and Dupont 2002;Guglielmin et al 2005;Borin et al 2010). Such rapid decay has been also documented physically through microrelief measurements (Dąbski 2015).…”
Section: Rock Surface Decaymentioning
confidence: 76%